In the work environment, can we motivate virtual/remote teams in the same way as co-located teams? - Lone, Kaiser (2017)
As organisations engage in developing and harnessing dynamic and motivated global team-based workforces, capable of transcending all conventional team-working barriers, the once unbridgeable frontier of geographical location has been fast overcome by technologies, digital tools, and services allowing team members to communicate, and interact with each other regardless of time and space.